Prevalence and Predictors of HCV among a Cohort of Opioid Treatment Patients in Dar es Salaam, Tanzania - Lambdin, Barrot H. (Int J Drug Policy, 2017)
BACKGROUND. The government of Tanzania launched an opioid treatment program (OTP), using methadone, in Dar es Salaam in February of 2011. Hepatitis C virus (HCV) is a leading cause of morbidity and mortality globally, especially among people who inject drugs (PWID). We conducted a cross-sectional study among PWID engaged in OTP in Dar es Salaam to describe the prevalence and predictors of HCV antibody serostatus. METHODS. Routine programmatic data on patients enrolled in Muhimbili National Hospital’s OTP clinic from February 2011 to January 2013 were utilized. Multivariable Poisson regression was used to examine factors associated with HCV antibody serostatus. RESULTS. A total of 630 PWID enrolled into the OTP clinic during the study period, seven percent of which were women. The overall seroprevalence of HCV antibody was 57% (95% Confidence interval: 53%-61%). In adjusted analysis, methadone patients who used heroin for 5-10 years (adjusted prevalence ratio; aPR=1.41; 95% CI: 1.10-1.81) and >10 years (aPR=1.48; 95% CI: 1.17-1.88) were more likely to be HCV antibody positive, compared to patients who used heroin for < 5 years. Patients who reported sharing needles or other equipment at their last injection (aPR=1.20; 95% CI: 1.01-1.41; p=0.022), being arrested (aPR=1.20; 95% CI: 1.04-1.40; p=0.012) and who were HIV-positive (aPR=1.84; 95% CI: 1.56-2.16; p<0.001) were also more likely to be HCV antibody positive than their counterparts. CONCLUSION. Our observed HCV antibody prevalence among PWID engaged in OTP is higher than previously reported estimates in Dar es Salaam. Predictors of HCV antibody serostatus in this sample were similar to those found among PWID in many other settings. Integrating HCV care and treatment into OTP clinics should be considered, leveraging lessons learned from the integration of HIV services into OTP. Global efforts to develop HCV care and treatment programs in low and middle-income countries are critical, especially among PWID who have a high burden of HCV.